The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1021/ol017022q
|View full text |Cite
|
Sign up to set email alerts
|

Direct Addition of TMS-acetylene to Aldimines Catalyzed by a Simple, Commercially Available Ir(I) Complex

Abstract: A new, convenient procedure for the addition reaction of trimethylsilylacetylene to imines is described. Simply treating a solution of aldimine and trimethylsilyl acetylene with catalytic [IrCl(COD)](2) furnishes the adduct in preparatively useful yields. Interestingly, the reaction may be conducted in the absence of solvent. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(70 citation statements)
references
References 31 publications
1
69
0
Order By: Relevance
“…[71][72][73] Interestingly, this was achieved by changing the catalytic system to RuCl 3 /Cu I . [73] The origin of the chemoselectivity is believed to be the inability of the indium(III) center to coordinate and activate the imine in water.…”
Section: Controlling the Fate Of Iminium Electrophilesmentioning
confidence: 99%
“…[71][72][73] Interestingly, this was achieved by changing the catalytic system to RuCl 3 /Cu I . [73] The origin of the chemoselectivity is believed to be the inability of the indium(III) center to coordinate and activate the imine in water.…”
Section: Controlling the Fate Of Iminium Electrophilesmentioning
confidence: 99%
“…When the same reaction was performed at 50 or 100 mmol scales, adduct 4a was isolated in slightly better yields (75 or 80%, respectively, entry 12). Using more CuCl did not significantly improve the yield of adduct 4a (entries [17][18][19][20], but using less catalyst caused the yield to be significantly lower under the same reaction conditions (entries [13][14][15][16]. Other catalysts that have previously been used in A 3 -coupling reactions were also tested using our optimized conditions, but only CuBr (entry 21) performed comparatively well.…”
Section: Resultsmentioning
confidence: 99%
“…It is also applicable to various substrates. This transformation can be catalyzed by a large number of transition-metal salts, including copper, 4 iron, 5 cobalt, 6 nickel, 7 zinc, 8 ruthenium, 9 silver, 10 cadmium, 11 indium, 12 ytterbium, 13 iridium, 14 gold, 15 mercury, 16 bimetallic salt combinations, 17 supported metals, 18 and nanostructured materials. 19 It is interesting to note that, although the use of various amines and aldehydes in this method has been described, the number of alkynes used has been limited.…”
mentioning
confidence: 99%
“…[4] Copper-catalyzed alkyne additions, disclosed by Li et al, also played a prominent role. [5] There have been a few examples of direct additions of alkynes to C=N electrophiles, in which an Ir, [6] Zr, [7] Ag [8] or Au [9] complex was used as a catalyst instead of a zinc or copper complex. Recently, Bolms group has described the dimethylzinc-mediated addition of terminal alkynes to imines without any ligands, [4l] Pedro et al reported a highly enantioselective zinc/BINOLcatalyzed alkynylation of N-sulfonylaldimines.…”
mentioning
confidence: 99%